공연예술 관람동기부여 요인과 관람만족 및 재관람 의사 간의 관계에서 관람몰입과 공연 만족도 효과 - 진석호(Seog-Ho Jin) (한국콘텐츠학회 논문지, 24(10), 2024)
본 연구의 주된 목적은 가능한 관객률을 최대화 하고, 확고한 관객층을 강화하는 것이다. 공연 예술 관람 동기 부여 요인이 관람몰입, 관람 만족 및 재관람 의사에 미치는 영향을 파악하는 것은 공연 예술 활성화에 도움이 되기 때문이다. 그래서 관람 동기 부여 요인과 관람 만족 및 재관람 의사 간의 관계에서 관람몰입과 공연 만족도 효과를 검증하고자 한다. 이러한 연구의 목적을 달성하기 위해 공연 예술을 관람한 경험이 있는 남, 녀를 대상으로 설문하였다. 이에 따른 결과는 다음과 같다. 공연예술 관람 동기 부여 요인 중 교육‧심미적, 현실도피 및 기분전환, 사회적 상호작용, 자존감 강화 요인과 관람만족 및 재관람 의사 간의 관계에서 관람몰입과 공연 만족도는 중요한 역할을 한다고 할 수 있다. The primary purpose of this study was to maximize the audience rate as high as possible and reinforce resolute audience base. Also, Identifying and determining the impact of motivating factors for viewing performing arts on viewing flow, viewing satisfaction, and intention to re-viewis to help the facilitation of performing arts. Therefore, we aim to verify the effect of viewing flow and performance satisfaction in the relationship between viewing motivation factors, viewing satisfaction, and re-watching intention. To achieve the purpose of this study, men and women who had experience watching performing arts were selected as the population. The results are as follows. Among the motivating factors for viewing performing arts, viewing flow and performance satisfaction can be said to play an indispensable role in the relationship between educational and aesthetic, escapism and diversion, social interaction, and self-esteem strengthening factors and viewing satisfaction and intention to re-view. KCI Citation Count: 0